Voluntary CSR disclosure, institutional environment, and independent audit demand - Peipei Zheng; Chunyan Ren (China Journal of Accounting Research, 2019)
Using a sample of A-share listed companies on the Shanghai and Shenzhen Stock Exchanges, this study examines the impact of voluntary corporate social responsibility (CSR) disclosure on independent audit demand in different institutional environments. The sample covers the 2008-2016 period and excludes firms that are required to disclose CSR information. The findings show that compared with companies that choose to not disclose such information, companies that voluntarily disclose CSR information prefer to employ "small" accounting firms for auditing services, although the auditing fees are much higher. However, as the institutional environment improves, this preference is weakened. Further analyses show that this preference is stronger in enterprises where CSR disclosure is driven by strong political motivations and managerial self-interest motivations. Legitimate motivations and economic motivations do not significantly impact the preference for "small" audit firms. Furthermore, this preference is more obvious in enterprises with poor operational performance and low information disclosure quality, and it increases as CSR disclosure level decreases. The study enriches our understanding of the economic consequences of voluntary CSR disclosure and the factors that influence independent audit demand. The results also have implications for the construction and regulation of China's system for supervising CSR information disclosure in the transitional phase.
Keywords: 650; Voluntary disclosure of corporate social responsibility information; Auditor selection; Auditing fees; Institutional environment